2019
DOI: 10.24106/kefdergi.3405
|View full text |Cite
|
Sign up to set email alerts
|

Fen Bilgisi Öğretmeni Adaylarının STEM Eğitimine İlişkin Metaforik Algıları

Abstract: Bu araştırmanın amacı fen bilgisi öğretmeni adaylarının STEM eğitimine ilişkin metaforik algılarını belirlemektir. Araştırmada betimsel tarama modeli kullanılmıştır. Araştırmanın çalışma grubunu 2016-2017 öğretim yılı bahar döneminde Ege bölgesindeki bir devlet üniversitesinin Fen Bilgisi Öğretmenliği Programına devam eden, 69 üçüncü sınıf öğrencisi oluşturmaktadır. Katılımcılara "STEM eğitiminin sahip olduğu özellikler düşünüldüğünde, STEM eğitimi ………'ya benzer; çünkü,……" yazılı bir form verilerek cümleyi tam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
7
0
4
Order By: Relevance
“…Interdisciplinary knowledge and learning experiences make a positive difference by establishing meaningful connections by using different viewpoints from various study fields (Eflanili, 2021). Previous studies findings in line with the 21st-century skills stated that interdisciplinary knowledge is important to find solutions for problem solving (Ergün & Kıyıcı, 2019), and different educational practices, professional support, and teamwork contribute to the creativeness of teachers and students to improve innovation as well (Braßler & Schultze, 2021). In addition, teachers and students can make progress in critical thinking, communication, creativity, pedagogy, and professional fields by using interdisciplinary techniques (Jones, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…Interdisciplinary knowledge and learning experiences make a positive difference by establishing meaningful connections by using different viewpoints from various study fields (Eflanili, 2021). Previous studies findings in line with the 21st-century skills stated that interdisciplinary knowledge is important to find solutions for problem solving (Ergün & Kıyıcı, 2019), and different educational practices, professional support, and teamwork contribute to the creativeness of teachers and students to improve innovation as well (Braßler & Schultze, 2021). In addition, teachers and students can make progress in critical thinking, communication, creativity, pedagogy, and professional fields by using interdisciplinary techniques (Jones, 2010).…”
Section: Discussionmentioning
confidence: 83%
“…Teacher candidates consider STEM as an interdisciplinary approach that moves forward, provides socialization and communication (Gokce & Yenmez, 2020). It was determined that teacher candidates perceived STEM as an interdisciplinary approach that provides learning by doing and experiencing in the process of creating new products and aims to raise individuals who produce solutions to problems (Ergun & Kiyici, 2019;Kizilay, 2018;Gomleksiz & Yavuz, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to increase the training that includes STEM-related applications and expand the scope of education (Eroglu & Bektas, 2016). It is stated that metaphors are used in a minority of STEM studies conducted with prospective teachers (Ergun & Kiyici, 2019). Considering these evaluations in the literature, it is thought that the study will contribute to the literature.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, there are studies showing that STEM awareness levels of teachers (Bölükbaşı and Görgülü Arı, 2019;Elayyan and Al-Shizawi, 2019;Ciğerci, 2020;Can and Uluçınar Sağır, 2018;Çevik, Danıştay and Yağcı, 2017), school administrators (Ciğerci, 2020) and university students (Hebebci and Usta, 2017) are positive. Additionally, it was determined that prospective teachers produced completely positive metaphors about STEM education in the metaphor studies related to STEM, they had positive opinions (Ergün and Kıyıcı, 2019a), and all prospective science teachers who got STEM education produced positive metaphors for STEM education (Altun Yalçın and Yalçın , 2018). In the study of Çalışıcı and Özçakır Sümen (2018), it was concluded in the metaphors produced by prospective classroom teachers that most of the prospective teachers believe STEM fields complement each other and are a useful approach.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%